Evaluation of Serum Glucose Concentrations, Hba1c, Urea, and Serum Creatinine in Individuals with Type 2 Diabetes in Samawah / Muthanna Governorate - Alfahad, Ahmed A. N. (American Journal of Biology and Natural Sciences, 2025)
This research was carried out between October 2023 and January 2024. A cross-sectional study took place at Samawah Teaching Hospital in Muthanna, Iraq. A total of 100 patient samples were chosen and categorized into four age groups: (less than 20, 20-40, 41-60, and more than 60). The impact of glycated was examined, focusing on their roles as screening tests and as the gold standard for evaluating glycemic control in individuals with diabetes and blood urea and creatinine levels were measured and compared with blood glucose concentrations. The results showed that blood sugar and HbA1c were high in all groups and there were significant differences between them in patients. Also, urea was high in all four groups, while creatinine was high in (G1) and (G3). The relationship between serum urea levels and blood glucose levels was found to be positive, with a correlation coefficient of r = +0.58. In contrast, when examining the correlation between serum creatinine levels and blood glucose in patients, a stronger positive correlation of r = +0.78 was observed. This research intends to evaluate the levels of bl00d sugar, HbA1c, ureaand creatinine, while also comparing the values across a four study groups. Furthermore, the study aims to explore the correlation between urea and creatinine levels and blood glucose concentrations in individuals diagnosed with type 2 diabetes.